Investigating the Shariah Approvals Issued by the Shariah Boards of Islamic Banks against the Parameters of Fatwa - Siddique, Muhammad Abubakar; Abdul Rashid (Islamic Banking and Finance Review, 2022)
On the contrary to its conventional counterpart, Islamic banks are bound to get Fatwā from its Shariah supervisory boards (SSBs) regarding the Shariah compliance of their operations, products and services. It is SSB that is responsible for any violation and circumvention of Shariah principles from Islamic banking side. Hence, to earn the trust of customers regarding Shariah compliance, the importance of Fatwās of SSB increases. In case of Pakistan, situation becomes ambiguous looking at the term ‘Shariah approval’ being used for Shariah ruling issued by SSB. It raises a question about juristic status of Shariah approval. The objective of the paper is to determine the juristic status of Shariah approval whether it is Fatwā or not? For this qualitative analytical approach is used. From four prominent manuals of Fatwā principles, parameters of Fatwā were extracted and applied on Shariah approvals. The study found that Shariah approvals are being considered as Fatwā because they announce the permissibility of Islamic banking operations, products, and services with duly signatures of Shariah advisors. It was also found that Shariah approvals do not fulfill prerequisites of Fatwā. The paper also draws the attention of regulators that detailed Fatwā is missing in Islamic banks. What exists is Shariah approval which only states that all matters of Islamic banks are Shariah compliant and lawful, but it does not possess any evidence and reference from the Qur’an, Sunnah and the books of jurists. These inefficient short Fatwā are defaming Islamic banking and hurting the public trust of its Shariah compliance.